Scholarly productivity in communication studies: a five-year review (2017–2021). Issue 1 (2nd January 2023) - Griffin, Darrin J.; Arth, Zachary W.; Bolkan, San; Gilbreath, James N.; Pike, Mackenzie P.; Hakim, Samuel D.
ABSTRACT: This study examined data from the years 2017–2021 in a sample of 24 journals in communication studies to determine normative and exceptional rates of publication. These data were examined using the traditional full counting method to determine research participation by assigning credit to each author, equally, when listed on a research publication. In addition, we examined the data to determine individual research contribution by using a weighted fractional count (WFC) to assign credit based on author order and the number of authors listed on a publication. Results indicated that most scholars in our sample of journals publish infrequently. Across five years, average rates of publication in our sample stand at 1.62 publications per active author with an average WFC of .72. Results also include metrics for central journals in our field where active scholars average 1.47 publications with a WFC of .49. Results are discussed in terms of institutional expectations.